KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSANPEMBELIAN PRODUK SEPATU MEREK YONGKI KOMALADIDI SURABAYA - YULIANA, EVA (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
In the era of globalization, business development has been marked by various types of competition. A phenomenon that occurs is that the need for fashionable look into the lifestyle of today’s society. A shoe is one of a complementary to our own fashion looks fashionable. Of various kinds of shoes, brand shoes Yongki Komaladi be one people’s choice. This research aims to determine the effect of product quality and price simultaneously and partially to the purchase decision of Yongki Komaladi Shoes. The results using the F test showed that simultaneous product quality and price affect purchasing decisions. It can be seen from the Adjusted R Square of 0.335. Then through the t test is known that the quality of products significantly influence purchasing decisions at 5.019 with a significance value of 0.000 <0.05 or 5%, while the price has amounted to 1,626 t value and not significantly influence the purchase decision as significance value of 0.107 which means> 0.05 or 5%. This shows that the quality of the partial products have a greater influence on purchasing decisions and prices have no influence on purchasing decisions. Keywords: Quality Product, Price, Purchase Decision.